Tuberculosis Diagnostics and Susceptibility in Saudi Arabia’s Western Region - Qutub, Mohammed; Wali, Ghassan; Alraddadi, Basem; Bahabri, Nezar; Aldabbagh, Yasser; Zaki, Sara; Mehdawi, Fahtima; Govindan, Prasanth; Vattappillil, Anupama; Alamoudi, Ebtihal (International Journal of Scientific Research and Management (IJSRM), 2020)
Introduction: Saudi Arabia has a moderate infection rate of tuberculosis (TB) in comparison to other countries in the region. The prevalence of TB varies among different parts of the Kingdom, with its western provinces reporting to have the leading rate of incidence.Method : In this retrospective study, Acid-fast bacilli smear (AFB), and nucleic acid amplification test (NAAT) were performed on all positive cultures from 254 identified TB cases from November 2006 to August 2016 in King Faisal Specialist Hospital and Research Center – Jeddah, Saudi Arabia.Results: From the positive cultures for Mycobacterium tuberculosis complex, 99.1% were found to be positive by using NAAT. From the NAAT positive samples, only 36.8% were positive for AFB. TB was predominant among the younger age group (59.4%) compared to the elderly population (35.8%) and pediatrics (4.7%), and it was also observed that males had a higher prevalence of 56.3 % in comparison to females. In regards to the site of infection, 53.1 % were pulmonary and 46.9% from an extrapulmonary. It was noted that resistance to first-line anti-TB drugs individually was found to be 11.0% to Streptomycin, 10.2% to isoniazid, 5.1% to pyrazinamide, 2.4% to Rifampicin, and 1.2% Ethambutol, yet multi-drug resistance (MDR) was found in 2.4% of observed cases.Conclusion: Young age predominance, low direct smear positivity, increased incidence of the extrapulmonary site of infection, and re-emergence of TB resistance all were observed in our study compared to previous national surveys.